2016
DOI: 10.1097/iae.0000000000001039
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Outcomes of a Novel Technique for Rescuing and Scleral Fixating a Posterior Dislocated Intraocular Lens–bag Complex Without Conjunctival Opening (Hoffman Pockets)

Abstract: Outcome data at 1 year support this novel technique as a viable option for the surgical repair of a dislocated lens-capsular bag complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…However, potential complications with this technique are numerous and include lens tilt, variability in lens location, suture erosion, lens dislocation, and potential opacification with air or gas. [ 20 21 22 23 24 25 26 27 28 ] Khan et al [ 16 ] described 84 eyes undergoing Gore-Tex suture scleral fixation of secondary IOL in the setting of PPV, with a similar rate of ocular hypertension occurring in their study: 3.6% of eyes vs. 4.4% in our study. Notably, they reported an increased rate of vitreous hemorrhage (7.1%) but a lower rate of postoperative CME (4.8%), compared with 0% and 8.8% in our study respectively.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…However, potential complications with this technique are numerous and include lens tilt, variability in lens location, suture erosion, lens dislocation, and potential opacification with air or gas. [ 20 21 22 23 24 25 26 27 28 ] Khan et al [ 16 ] described 84 eyes undergoing Gore-Tex suture scleral fixation of secondary IOL in the setting of PPV, with a similar rate of ocular hypertension occurring in their study: 3.6% of eyes vs. 4.4% in our study. Notably, they reported an increased rate of vitreous hemorrhage (7.1%) but a lower rate of postoperative CME (4.8%), compared with 0% and 8.8% in our study respectively.…”
Section: Discussionsupporting
confidence: 72%
“…Notably, they reported an increased rate of vitreous hemorrhage (7.1%) but a lower rate of postoperative CME (4.8%), compared with 0% and 8.8% in our study respectively. Budoff et al [ 22 ] report on 19 eyes undergoing SFIOLs, showed IOL decentration occurred in 3 eyes, Vitreous hemorrhage occurred in 4 eyes, and CME occurred in 4 eyes. Abbey et al [ 20 ] reported 23 eyes with sutureless scleral fixation of IOLs, with similar rates of macular edema (8.7%) compared with our study and a similar rate of vitreous hemorrhage compared with Budoff et al [ 22 ] and Khan et al [ 16 ] None of their patients had significant preoperative ocular comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This haptic can not only prevent slippaging of knot along the haptic, but also prevent continuous cutting force induced by monofilament suture across the haptic [17]. Fourthly, the haptic loop was 10 degree backward angled with the optic, and then the optic was kept away from the iris to avoid chafing of the iris or ciliary body after suture fixation [18]. No pigment dispersion or glaucoma was found in our patients during their follow-up period, although pigment dispersion and pigmentary glaucoma are more prone to those undergo transscleral suture fixation of PCIOLs [19].…”
Section: Discussionmentioning
confidence: 99%